On the principle of comparison and estimates of the Lyapunov functions for nonlinear systems - Martynyuk, A.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
Some new estimates of the Lyapunov function for a nonlinear system and conditions of Lyapunov stability and stability on a finite interval are established. The above conditions are based on estimates of the norms of solutions of a nonlinear system of equations of perturbed motion.